Synechococcus: 3 billion years of global dominance - Dvořák, Petr; Casamatta, Dale A; Poulíčková, Aloisie; Hašler, Petr; Ondřej, Vladan; Sanges, Remo (Molecular ecology, 2014)
Cyanobacteria are among the most important primary producers on the Earth. However, the evolutionary forces driving cyanobacterial species diversity remain largely enigmatic due to both their distinction from macro-organisms and an undersampling of sequenced genomes. Thus, we present a new genome of a Synechococcus-like cyanobacterium from a novel evolutionary lineage. Further, we analyse all existing 16S rRNA sequences and genomes of Synechococcus-like cyanobacteria. Chronograms showed extremely polyphyletic relationships in Synechococcus, which has not been observed in any other cyanobacteria. Moreover, most Synechococcus lineages bifurcated after the Great Oxidation Event, including the most abundant marine picoplankton lineage. Quantification of horizontal gene transfer among 70 cyanobacterial genomes revealed significant differences among studied genomes. Horizontal gene transfer levels were not correlated with ecology, genome size or phenotype, but were correlated with the age of divergence. All findings were synthetized into a novel model of cyanobacterial evolution, characterized by serial convergence of the features, that is multicellularity and ecology.
Keywords: horizontal gene transfer; speciation; přenos genů horizontální; fylogeneze; RNA, Ribosomal, 16S; genome; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Genome, Bacterial; cyanobacteria; molekulární sekvence - údaje; biologická evoluce; sekvenční seřazení; Gene Transfer, Horizontal; genom bakteriální; 16S rRNA; Synechococcus; DNA, Bacterial; DNA bakterií; Biological Evolution; evolution; RNA ribozomální 16S; Molecular Sequence Data; Sequence Alignment